2021
DOI: 10.1128/jvi.00666-21
|View full text |Cite
|
Sign up to set email alerts
|

Headless Henipaviral Receptor Binding Glycoproteins Reveal Fusion Modulation by the Head/Stalk Interface and Post-receptor Binding Contributions of the Head Domain

Abstract: Cedar virus (CedV) is a nonpathogenic member of the Henipavirus (HNV) genus of emerging viruses, which includes the deadly Nipah (NiV) and Hendra (HeV) viruses. CedV forms syncytia, a hallmark of henipaviral and paramyxoviral infections and pathogenicity. However, the intrinsic fusogenic capacity of CedV relative to NiV or HeV remains unquantified. HNV entry is mediated by concerted interactions between the attachment (G) and fusion (F) glycoproteins. Upon receptor binding by the HNV G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Different characteristics among closely related viruses can be utilized in comparative functional investigations to understand aspects of henipavirus biology such as evolution, host tropism, cross-species transmission and pathogenicity. So far CedV ( Marsh et al, 2012 ; Lieu et al, 2015 ; Laing et al, 2018 , 2019 ; Schountz et al, 2019 ; Yeo et al, 2021 ), KV ( Pernet et al, 2014a ; Lee et al, 2015 ) and MojV ( Rissanen et al, 2017 ; Cheliout Da Silva et al, 2021 ) have been involved in a number of such studies. Non-pathogenic henipa-like viruses such as CedV could also be used as immunogen vectors in vaccines against pathogenic henipavirus disease, since antigenic overlap could induce cross-reactivity between closely related viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Different characteristics among closely related viruses can be utilized in comparative functional investigations to understand aspects of henipavirus biology such as evolution, host tropism, cross-species transmission and pathogenicity. So far CedV ( Marsh et al, 2012 ; Lieu et al, 2015 ; Laing et al, 2018 , 2019 ; Schountz et al, 2019 ; Yeo et al, 2021 ), KV ( Pernet et al, 2014a ; Lee et al, 2015 ) and MojV ( Rissanen et al, 2017 ; Cheliout Da Silva et al, 2021 ) have been involved in a number of such studies. Non-pathogenic henipa-like viruses such as CedV could also be used as immunogen vectors in vaccines against pathogenic henipavirus disease, since antigenic overlap could induce cross-reactivity between closely related viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Henipavirus and Morbilivirus genera, the attachment and fusion proteins are believed to form complexes prior to receptor engagement (33) (Figure 5A). While this might suggest a mechanism where the attachment protein functions as a clamp on the fusion protein, maintaining the pre-fusion state before receptor binding, studies assaying fusion competency have demonstrated that the fusion protein alone is not sufficient for virus and host cell fusion, indicating that fusion triggering involves a more complex mechanism of interaction between the two proteins (9,48).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with the cytoskeleton also modulate cell-cell fusion, as highlighted by proteomics [61]. The study of HNV mutants also revealed that the early and late steps of the membrane fusion cascade are modulated by several regions of G head and stalk domains [31,32,48] and of F [62,63]. Furthermore, N-and O-glycans in most paramyxoviral glycoproteins have been shown to modulate protein expression, folding, and transport; for HNVs in particular, several N-and O-glycans in NiV and HeV G and F modulate virus-cell and cell-cell fusion independently of protein expression [64][65][66].…”
Section: The Molecular Prerequisites Of Syncytium Formationmentioning
confidence: 99%
“…Although a wide range of cell lines are susceptible to HNV-induced cell-cell fusion and qualitative patterns (susceptible versus refractory to cell-cell fusion) seem conserved across HNVs, quantitative variations have been reported. For instance, CedV induces significantly less cell-cell fusion than NiV in human kidney HEK293T cells [48]. Similarly, KuV and MojV also appear to form fewer syncytia than NiV in HEK293T and hamster kidney BHK cells [23,57].…”
Section: Occurrence Of Henipavirus-induced Syncytia Across Viruses and Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation